PENGARUH VARIASI KAPASITAS PEMANAS TERHADAP KONDISI SUHU DAN KELEMBABAN SERTA DURASI PEMANASAN PADA SCREENHOUSE BERBASIS EVAPORATIVE COOLING SYSTEM - Wirenda Sekar Ayu; Muhamad Anda Falahuddin; Windy Hermawan Mitrakusuma; Dian Anggraeni (Jurnal Teknologi Terapan, 2023)
The unpredictable weather changes in Indonesia cause various problems for the agricultural sector. One of which is the decline in productivity of farmers' crops up to 40% which is caused by non-optimal environmental conditions during the plant growth process. To be able to adapt to these conditions, it is necessary to have an optimal system of environmental conditioning for plant growth. In this research, a screenhouse temperature and humidity conditioning system was designed for the growth of tomato plants as a horticultural commodity with high potential and high economic value in Indonesia. The system design is modeled and tested through simulation on Vensim software by varying the furnace capacity by 4oC/hour, 6oC/hour, and 10oC/hour in order to see its effect on the internal screenhouse temperature and heating duration. Based on the simulation results of system design, the heating rate and duration for each furnace capacity variation are 4.74oC/hour (135 minutes per cycle), 6.9oC/hour (75 minutes per cycle), and 11.76oC/hour (45 minutes per cycle). The furnace capacity value of 10oC/hour is considered to be optimal and more energy efficient because it only requires a heating process for 180 minutes per day to maintain the screenhouse internal temperature in optimal temperature range for tomato plant growth, which is 18 - 24 oC with an offside value of ±0.5 oC. The stable cooling rate value for this system is in the range of 1 – 1.8oC/hour.